2020
DOI: 10.1101/2020.12.15.20248264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a Rapid Point-Of-Care Test that Measures Neutralizing Antibodies to SARS-CoV-2

Abstract: As increasing numbers of people recover from and are vaccinated against COVID-19, tests are needed to measure levels of protective, neutralizing antibodies longitudinally to help determine duration of immunity. We developed a lateral flow assay (LFA) that measures levels of neutralizing antibodies in plasma, serum or whole blood. The LFA is based on the principle that neutralizing antibodies inhibit binding of the spike protein receptor-binding domain (RBD) to angiotensin-converting enzyme 2 (ACE2). The tes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Lateral flow assays are commonly used for rapid clinical testing, such as COVID-19 serological tests, antigen tests, certain molecular tests, and the neutralizing antibody test [ 29 , 30 , 31 , 32 , 33 ]. Wang et al reported on the use of a lateral flow dipstick assay with wild-type and the South African spike S1 protein for the characterization of the neutralizing activity of post-vaccination plasma samples [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lateral flow assays are commonly used for rapid clinical testing, such as COVID-19 serological tests, antigen tests, certain molecular tests, and the neutralizing antibody test [ 29 , 30 , 31 , 32 , 33 ]. Wang et al reported on the use of a lateral flow dipstick assay with wild-type and the South African spike S1 protein for the characterization of the neutralizing activity of post-vaccination plasma samples [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our studies demonstrated that sandwich-based immunoassays, such as lateral flow assays, offer an attractive and cost-effective alternative in characterizing the antibody binding properties, epitope binning, and in vitro neutralizing kinetics of therapeutic antibodies and cocktails. Lake et al and others have demonstrated that the lateral flow-based (surrogate) neutralizing antibody test performs similarly to the pseudo-virus or the authentic SARS-CoV-2 virus-based neutralizing antibody assays in assessment of the neutralizing antibody activity of convalescent samples against SARS-CoV-2 [ 29 , 30 ]. Therefore, our lateral flow-based rapid neutralizing antibody tests could potentially be used to assess the neutralizing antibody activities against the SARS-CoV-2 RBD and the UK, SA, and BR P.1 variant RBDs in human blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral flow assays are commonly used for rapid clinical testing, such as COVID-19 serological tests, antigen tests, certain molecular tests, and the neutralizing antibody test [29][30][31][32][33]. Wang et al have reported the use of a lateral flow dipstick assay with wild-type and the South African spike S1 protein for the characterization of the neutralizing activity of post-vaccination plasma samples [29].…”
Section: Discussionmentioning
confidence: 99%
“…This simplifies testing reactivity against RBD variants of concern, since no labeling is required. A more fundamental advantage, as illustrated by the simulations in Fig 1d and Extended Data Fig 1 , is that compared to ternary sensor systems that rely on direct competition of the ACE-2:RBD interaction by neutralizing antibodies, our quaternary sensor system can more readily distinguish analyte binding affinity and abundance 17 , both of which are relevant for diagnosing the success of vaccination. Distinguishing signals due to higher concentrations of more weakly binding analytes from those due to lower concentrations of more strongly binding analytes is challenging for a simple competition mechanism because the extent of competition depends on the ratio of competitor concentration to the Kd.…”
Section: Mainmentioning
confidence: 99%